Menggali Nilai-Nilai Etika, Akhlak, Dan Tanggung Jawab Sosial Pada Lembaga Pendidikan Islam - Hayati, Nur; Zahroh, Ifqotus (Universitas Pakuan, 2025)
EXPLORING ETHICAL VALUES, MORALITY, AND SOCIAL RESPONSIBILITY IN ISLAMIC EDUCATIONAL INSTITUTIONS Islamic education holds a highly strategic position in shaping students’ character, particularly through the internalization of fundamental values that encompass ethics, morality, and social responsibility. This strategic role is evident in its ability to guide learners not only toward cognitive competence but also toward moral and spiritual development, which serves as the foundation of a holistic personality. In this context, this article seeks to comprehensively examine the value foundations in Islamic education, including the normative principles that guide character formation. The discussion also focuses on how these values are implemented in the formal curriculum and within the educational environment through learning processes, habitual practices, and the exemplary conduct of educators which together function as a medium for value internalization. This article further analyzes the relevance of instilling ethical, moral, and social responsibility values in forming a generation that possesses not only intellectual intelligence but also noble character, integrity, and social awareness. Findings from the analysis indicate that integrating Islamic values into all aspects of educational implementation from curriculum planning and execution to the model provided by educators and the development of a religious and ethical institutional culture significantly contributes to the creation of insan kamil, individuals who embody a balance of intellectual, spiritual, moral, and social dimensions. Moreover, this article strengthens its scholarly arguments by drawing on empirical references from various indexed journals published within the last five years. As a result, the analysis presented is not only grounded in strong theoretical foundations but is also validated by contemporary research findings relevant to the current developments in Islamic education.